Africa's Lions Growth Traps and Opportunities for Six African Economies - Bhorat, Haroon; Tarp, Finn (Brookings Institution Press, 2016)
Africa's Lions examines the economic growth experiences of six fast-growing and/or economically dominant African countries. Expert African researchers offer unique perspectives into the challenges and issues in Ethiopia, Ghana, Kenya, Mozambique, Nigeria, and South Africa.Despite a growing body of research on African economies, very little research has focused on the relationship between economic growth and employment outcomes at the detailed country level. A lack of empirical data has, in many cases, deprived policymakers of a robust evidence base on which to make informed decisions. By harnessing country-level household, firm, and national accounts data, together with existing analytical country research, the authors have attempted to bridge this gap.